Environmentally Friendly Technological Innovations in The Form of Botanical Pesticides and Biological Pesticides for Cocoa Plants in Ransiki Tourism Areas - Sutiharni; Martanto, Eko Agus; Bodang, Yacob; Tanati, Adelin Elsina (Indonesian Journal of Community Services Cel, 2022)
Ransiki area is the capital of South Manokwari regency which has tourism potential with its exotic natural beauty so that it is visited by many tourists. In addition, the area has a lot of endemic plant diversity that has the potential to produce secondary metabolic compounds, one of which is black fruit trees (pohon buah hitam). The leaves of the black fruit tree contain secondary metabolic compounds of tannins (8.34-37.26%), more than flavonoids and alkaloids. For the development of environmentally friendly technological innovations, the Faculty of Agriculture UNIPA continues to develop black fruit tree leaves as liquid and powder botanical pesticides, as well as the biological pesticide from Trichoderma sp with inoculum sources obtained around the cocoa plantation in the Ransiki area. Cocoa plants are managed by indigenous people, immigrants and companies/cooperatives, have produced food products in the form of chocolate bars and cocoa powder, have potential for regional income and sales have reached overseas. Community service activities carried out from October to December 2021, use counseling methods, technical guidance/training, dissemination, and demonstration plot, mentoring. This activity is in line with the increasing promotion of tourist attractions in the Ransiki area, aiming to introduce and utilize regional superior agricultural products that can be applied to cocoa plants. Furthermore, it is expected to provide an increase in regional income, welfare of farmers and companies/cooperatives, and improve the quality of cocoa products from organic farming towards sustainable agricultural development. The application of botanical pesticides in cocoa plantations has proven to be able to control cocoa pod sucking ladybugs (Helopelthis spp), stem borers (Zeuzera coffea), and the dissemination of pesticide products are used as guidelines for preparing work plans for the Department of Agriculture, Cooperatives, Industry and Trade, South Manokwari Regency